The Structure of Preferences of Olive Oil Importers: The Country of Origin Effect. Issue 7 (1st September 2020) - Chamorro-Mera, Antonio; Román-Suero, Beatriz; García-Galán, María Del Mar
ABSTRACT: This study analyzes the structure of preferences of olive oil importers in three countries (USA, Germany and Mexico, three non-producer countries with very different cultural characteristics) to evaluate the country of origin effect in their purchasing decisions. Using the conjoint analysis technique, the data collected through a survey sent to the list of importers in the "Alimentos de Extremadura- Food from Spain " project, a total of 31 companies, is analyzed. From the study of the origin, packaging, production system and price attributes, the overall results show that origin is the attribute most valued by the importers, very closely followed by price. The analysis carried out shows that the country of origin effect is not universal. Exporters of olive oil need more than one marketing-mix strategy and they may also be very useful for both business managers and for those responsible in the public administrations for managing trade policies.